Post Dural Puncture Headache pada Spinal Anestesi - Khaira Maulina; Anna Millizia (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Spinal anesthesia is one of the commonly used methods of neuraxial anesthesia, especially in surgical procedures in areas of the lower body. This technique is performed by injecting a local anesthetic drug directly into the intrathecal space (subaraknoid), which is under the dura mater layer. Although effective and relatively safe, this procedure has a risk of complications, one of which is Postdural Puncture Headache (PDPH). PDPH is a typical headache condition, occurring due to a tear in the dura mater that causes cerebrospinal fluid (CSS) leakage. The loss of this CSS leads to a significant decrease in intracranial pressure, thus triggering the onset of headaches that usually worsen when the patient is sitting or standing, and subside when lying down. The incidence rate of PDPH is reported to range from 10–25%, depending on the type of needle used, age, gender, and the technique of the procedure performed by the operator. The diagnosis of PDPH can generally be established through an anamnesis and physical examination without the need for supporting examinations such as laboratory or imaging. Initial management of PDPH is usually conservative, such as oral and intravenous hydration, analgesics, caffeine, and recommendations for bed rest in a supine position. If symptoms do not improve, epidural blood patch (EBP) can be a very effective and widely recommended definitive option. To reduce the incidence of PDPH, various innovations have been made in the design of the spinal needle. Needles with non-cutting tips such as pencil-point needles (e.g. Sprotte or Whitacre) have been shown to be less likely to cause PDPH than cutting needles (such as Quincke). Therefore, the selection of the right needle and the skill of the operator play an important role in the prevention of PDPH, in order to improve patient comfort, safety, and safety during spinal anesthesia procedures.